2016
DOI: 10.12688/f1000research.9534.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding Streptomyces

Abstract: About 2,500 papers dated 2014–2016 were recovered by searching the PubMed database for Streptomyces, which are the richest known source of antibiotics. This review integrates around 100 of these papers in sections dealing with evolution, ecology, pathogenicity, growth and development, stress responses and secondary metabolism, gene expression, and technical advances. Genomic approaches have greatly accelerated progress. For example, it has been definitively shown that interspecies recombination of conserved ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
177
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(181 citation statements)
references
References 138 publications
(194 reference statements)
2
177
0
2
Order By: Relevance
“…In plants, via metal nitrosylation, S-nitrosylation and tyrosine nitration, NO influences physiological key processes including growth and development, seed dormancy/germination, photosynthesis, flowering and stomatal movement (see reviews Besson-Bard et al 2008;Koul et al 2014). Furthermore, NO can also affect the growth of bacteria by manipulating their antibiotic resistance, promoting their antibiotic production, representing a developmental regulatory element and/or leading to an adaption to oxidative stress; all these features can indirectly influence the interference between bacteria and plants (Table 3) (Gusarov and Nudler 2005;Gusarov et al 2008;Chater 2016;Sasaki et al 2016). For instance, low concentrations of NO lead to dispersal of biofilm, increased cell motility or biofilm enhancement, features, which play an important role in plant root colonization (Barraud et al 2009;Liu et al 2012;Arruebarrena Di Palma et al 2013;Henares et al 2013).…”
Section: Nitric Oxidementioning
confidence: 99%
“…In plants, via metal nitrosylation, S-nitrosylation and tyrosine nitration, NO influences physiological key processes including growth and development, seed dormancy/germination, photosynthesis, flowering and stomatal movement (see reviews Besson-Bard et al 2008;Koul et al 2014). Furthermore, NO can also affect the growth of bacteria by manipulating their antibiotic resistance, promoting their antibiotic production, representing a developmental regulatory element and/or leading to an adaption to oxidative stress; all these features can indirectly influence the interference between bacteria and plants (Table 3) (Gusarov and Nudler 2005;Gusarov et al 2008;Chater 2016;Sasaki et al 2016). For instance, low concentrations of NO lead to dispersal of biofilm, increased cell motility or biofilm enhancement, features, which play an important role in plant root colonization (Barraud et al 2009;Liu et al 2012;Arruebarrena Di Palma et al 2013;Henares et al 2013).…”
Section: Nitric Oxidementioning
confidence: 99%
“…They evolved filamentous growth ca. 440 mya when plants were first colonising land and it has been suggested that this enabled them to successfully colonise plant roots (Chater 2016). Several studies have reported that streptomycetes are abundant inside the roots of the model plant Arabidopsis thaliana (Bai et al 2015, Bodenhausen et al 2013, Bulgarelli et al 2012, Carvalhais et al 2015, Lebeis et al 2015, Lundberg et al 2012, Schlaeppi et al 2014), and others have shown that streptomycetes can protect crop plants such as strawberry, lettuce, rice, and wheat against biotic and abiotic stressors, including drought, salt stress, and fungal pathogens (see Schrey and Tarkka 2008, Viaene et al 2016 for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…This feature makes S. venezuelae ideally suited for large scale 'omics' technologies. Regulons controlled by several of the major transcription factors governing aerial mycelium and spore formation have now been mapped by application of ChIP-seq and transcriptomics in S. venezuelae (Bibb et al, 2012;Bush et al, 2013;2016;Al-Bassam et al, 2014). Following from recent papers of this type, the study by Bush et al (2017) describes the discovery of an intriguing regulatory layer involved in fine-tuning the initiation of sporulation.…”
Section: Streptomyces Venezuelaementioning
confidence: 99%